# 3x^2+5x-13=11-9x

## Simple and best practice solution for 3x^2+5x-13=11-9x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 3x^2+5x-13=11-9x equation:

Simplifying
3x2 + 5x + -13 = 11 + -9x

Reorder the terms:
-13 + 5x + 3x2 = 11 + -9x

Solving
-13 + 5x + 3x2 = 11 + -9x

Solving for variable 'x'.

Reorder the terms:
-13 + -11 + 5x + 9x + 3x2 = 11 + -9x + -11 + 9x

Combine like terms: -13 + -11 = -24
-24 + 5x + 9x + 3x2 = 11 + -9x + -11 + 9x

Combine like terms: 5x + 9x = 14x
-24 + 14x + 3x2 = 11 + -9x + -11 + 9x

Reorder the terms:
-24 + 14x + 3x2 = 11 + -11 + -9x + 9x

Combine like terms: 11 + -11 = 0
-24 + 14x + 3x2 = 0 + -9x + 9x
-24 + 14x + 3x2 = -9x + 9x

Combine like terms: -9x + 9x = 0
-24 + 14x + 3x2 = 0

Factor a trinomial.
(-6 + -1x)(4 + -3x) = 0

Subproblem 1Set the factor '(-6 + -1x)' equal to zero and attempt to solve:

Simplifying
-6 + -1x = 0

Solving
-6 + -1x = 0

Move all terms containing x to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + -1x = 0 + 6

Combine like terms: -6 + 6 = 0
0 + -1x = 0 + 6
-1x = 0 + 6

Combine like terms: 0 + 6 = 6
-1x = 6

Divide each side by '-1'.
x = -6

Simplifying
x = -6
Subproblem 2Set the factor '(4 + -3x)' equal to zero and attempt to solve:

Simplifying
4 + -3x = 0

Solving
4 + -3x = 0

Move all terms containing x to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + -3x = 0 + -4

Combine like terms: 4 + -4 = 0
0 + -3x = 0 + -4
-3x = 0 + -4

Combine like terms: 0 + -4 = -4
-3x = -4

Divide each side by '-3'.
x = 1.333333333

Simplifying
x = 1.333333333Solutionx = {-6, 1.333333333}`